2021
DOI: 10.3389/fpsyg.2021.659434
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Language Proficiency in False Memory: A Mini Review

Abstract: Memory errors and, specifically, false memories in the Deese/Roediger–McDermott paradigm have been extensively studied in the past decades. Most studies have investigated false memory in monolinguals’ native or first language (L1), but interest has also grown in examining false memories in participants’ second language (L2) with different proficiency levels. The main purpose of this manuscript is to review the current state of knowledge on the role of language proficiency on false memories when participants en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 101 publications
4
10
0
Order By: Relevance
“…This greater activation of the critical lures from words in the L1, as compared to the L2, would lead to a greater false recognition of L1 critical lures during the memory test [ 40 ]. This is precisely the result found in the few previous studies on the effect of language dominance on false recognition (for a review, see [ 39 ]).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This greater activation of the critical lures from words in the L1, as compared to the L2, would lead to a greater false recognition of L1 critical lures during the memory test [ 40 ]. This is precisely the result found in the few previous studies on the effect of language dominance on false recognition (for a review, see [ 39 ]).…”
Section: Introductionsupporting
confidence: 87%
“…Although these two lines of research, the second language processing and the false memory, have been extensively studied separately, there is a scarcity of studies examining false memories in the first language (hereafter L1) as compared to the second language (hereafter L2). Precisely, a recent review conducted by Suarez and Beato [ 39 ] only found eight articles in the literature examining this topic. Despite the heterogeneity of the studies found in terms of language dominance, language proficiency, and age of the participants, the results of the review seem to point out that false memories occur more often in the L1 or dominant language than in the L2 or non-dominant language.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the degree of misinformation acceptance in English showed significant differences suggesting that the misinformation effect was greater for the High-proficient group than for the Intermediate group. A recent review of false memories in the bilingual Deese-Roediger-McDermott (DRM)paradigm by Suarez and Beato (2021), also found that false memories are greater in participants with higher proficiency compared to the ones with lower levels and do not differ when the command of the participants in both the languages is similar. Importantly, the authors propose that it is not proficiency per se but rather dominance and environmental and interactional context that plays a major role in such differences (Beatty-Martínez et al, 2020;Suarez and Beato, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the focus of prior work has been on how language proficiency can impact the “activation” process of these kinds of false memories, as one's dominant language is thought to contain stronger word associations and/or conceptual relationships or gist that could activate the critical lure compared with one's foreign language. Suarez and Beato (2021) recently provided an insightful metanalysis of the bilingualism literature in DRM, with a focus on the likelihood of false memories in one's native versus foreign language. The overarching pattern identified by Suarez and Beato (2021) was that false memories in the DRM task were more likely when participants processed the material in their native tongue compared with their foreign tongue, at least when the native tongue was the more dominant language.…”
Section: Study 1: Impact Of Foreign Language On a Modified Drm Taskmentioning
confidence: 99%
“…David A Gallo contributed equally to meth-Yet emerging literature indicates that the language used during memory tasks can impact susceptibility to false memories. As discussed more extensively below, this literature has focused on the strength of conceptual associations in one language versus the other, using tasks that rely on preexisting associations to elicit false memories (Anastasi et al, 2005;Arndt & Beato, 2017;Howe et al, 2008;Sahlin et al, 2005; for a meta-analysis, see Suarez & Beato, 2021). This work is important for showing how language can activate false memories based on the strength of word associations, but we hypothesized that foreign language might have an even broader impact on information processing.…”
mentioning
confidence: 99%